An endophyte of Macrochloa tenacissima (esparto or needle grass) from Tunisia is a novel species in the Fusarium redolens species complex. (3rd July 2020) - Gargouri, Samia; Balmas, Virgilio; Burgess, Lester; Paulitz, Timothy; Laraba, Imane; Kim, Hye-Seon; Proctor, Robert H.; Busman, Mark; Felker, Frederick C.; Murray, Timothy; O'Donnell, Kerry
ABSTRACT: Here, we report on the morphological, molecular, and chemical characterization of a novel Fusarium species recovered from the roots and rhizosphere of Macrochloa tenacissima (halfa, esparto, or needle grass) in central Tunisia. Formally described here as F. spartum, this species is a member of the Fusarium redolens species complex but differs from the other two species within the complex, F. redolens and F. hostae, by its endophytic association with M. tenacissima and its genealogical exclusivity based on multilocus phylogenetic analyses. To assess their sexual reproductive mode, a polymerase chain reaction (PCR) assay was designed and used to screen the three strains of F. spartum, 51 of F. redolens, and 14 of F. hostae for mating type ( MAT ) idiomorph. Genetic architecture of the MAT locus in the former two species suggests that if they reproduce sexually, it is via obligate outcrossing. By comparison, results of the PCR assay indicated that 13/14 of the F. hostae strains possessed MAT1-1 and MAT1-2 idiomorphs and thus might be self-fertile or homothallic. However, when the F. hostae strains were selfed, 11 failed to produce perithecia and one only produced several small abortive perithecia. Cirrhi with ascospores, however, were only produced by 8/28 and 4/84 of the variable size perithecia, respectively, of F. hostae NRRL 29888 and 29890. The potential for the three F. redolens clade species to produce mycotoxins, pigments, and phytohormones was assessed by screening whole genome sequence data and by analyzing extracts on cracked maize kernel cultures via liquid chromatography–mass spectrometry.